Maternal Risk Factors Associated with Neonatal Stunting: A Case–Control Study - Anita Rohhmah; Yasmini Fitriyati; Afifah Az Zahra; Isna Arifah Rahmawati (Indonesian Socety of Obstetrics and Gynecology, 2026)
AbstractObjective: To identify maternal risk factors associated with neonatal stunting at Wonosari Hospital. Methods: A case–control study was conducted involving mothers who gave birth at Wonosari Hospital in 2023. Maternal sociodemographic characteristics (age, education, and occupation), nutritional status (body mass index and mid-upper arm circumference), and pregnancy-related factors (gestational age, gestational status, hemoglobin levels, blood pressure, pregnancy complications, and mode of delivery), as well as newborn length at birth, were obtained from medical records. Neonatal stunting was defined as a length-for-age z-score < ?2 SD according to World Health Organization (WHO) standards. Statistical analysis was performed using chi-square tests and multiple logistic regression. Results: A total of 154 participants were included, equally divided into case (stunted newborns) and control (non-stunted newborns) groups. Mothers with a lower educational level had significantly higher odds of delivering a stunted newborn (p= 0.010; aOR = 2.845; 95% CI = 1.286–6.293). Preterm birth was also associated with an increased risk of neonatal stunting (p= 0.033; aOR = 9.847; 95% CI = 1.210–80.152). In addition, pregnancy complications were significantly associated with higher odds of neonatal stunting (p = 0.020; aOR = 2.728; 95% CI = 1.171–6.352). Conclusion: Maternal factors, including low educational level, preterm birth, and pregnancy complications, were significantly associated with neonatal stunting at Wonosari Hospital. These findings underscore the importance of maternal education in neonatal health outcomes. Furthermore, close monitoring of fetal growth and nutritional status, along with appropriate management of pregnancy complications, may help reduce the risk of neonatal stunting. However, larger-scale studies are needed to assess the population-level impact of these factors. Keywords: neonatal, pregnancy complication, stunting.